Assessment of accumulation of petroleum hydrocarbons by the hydrobionts of the south-eastern part of the Onega bay of the White sea - N. V. Neverova; T. Ya. Vorobyeva; A. V. Chupakov; Н. В. Неверова; Т. Я. Воробьева; А. В. Чупаков (Arctic and Antarctic Research, 2019)
In order to assess the current state of the ecosystem of the southeast of the Onega Bay of the White Sea affected by fuel oil spill in 2003, the accumulation of petroleum hydrocarbons was analyzed by the dominant species of aquatic organisms collected on the littoral of the most polluted coast in the areas of Purnem and Lyamts villages. In 2012, samples of aquatic organisms were taken in an area where all the species discussed in this work are represented on a small area: bivalved mollusks, attached molluscs, gastropods, polychaetes. In 2013 and 2018, samples of hydrobionts were additionally selected, in the three-kilometer strip of the coast on either sides of the givin point. In 2012 and 2013, high concentrations of HC in the tissues of bivalves were recorded. In 2018, the concentrations of hydrocarbons in the tissues of the studied hydrobionts were comparable to background values. A non-parametric test of Mann-Whitney showed a significant decrease in НС in mussel tissue from 2013 to 2018, at a significance level of 0.05. Taking into account the low levels of HC in the aqueous medium (less than 1 MPC of fishfarm) and in bottom sediments (from 0.34 to 9.03 mg/kg, the median of 1.41 mg/kg) in 2018, and is comparable with the background contents of hydrocarbons in tissues of aquatic organisms. We can conclude that after 15 years of the fuel oil spill, the condition of the Cape Deep ecosystem in terms of the content of hydrocarbons returns to the baseline state, continuing emissions of oil-sand lumps do not adversely affect the ecosystem. Based on the work done, it can also be concluded that ecotoxocological methods are priority in assessing the prolonged (or delayed) accidental impact of heavy petroleum products on aquatic ecosystems. The conclusion about the presence or absence of a negative impact on the aquatic ecosystem of hydrocarbons, based solely on the analysis of abiotic components, may not be sufficiently informative because it does not take into account the accumulative and deferred effects, especially ...